Parental awareness on cyber threats using social media - Nazilah Ahmad@Ahmad Arifin; Umi Asma’ Mokhtar; Zaihosnita Hood; Sabrina Tiun; Dian Indrayani Jambari (Penerbit Universiti Kebangsaan Malaysia, 2019)
In recent years, the use of Internet has increased exponentially and most of the users are from adolescents. Internet technology has facilitated cyber threats activities and many of the cases are from adolescents. Users at this age need parental guidance and support because they are still naïve or immature to understand the risks of Internet. Hence, many developed countries have imposed on clear guidelines on the Internet to control and guide the users and understand the risks they will encounter when they are online. The guidance on how to use the Internet or social media begins at home and requires parental involvement to educate the children. Therefore, this study attempts to investigate on the parental knowledge and readiness whether they aware of the risks of Internet to their children. The level of parental awareness can be correlated with cyber safety at home. It is important to identify the awareness as one of the early cyber threat prevention. This study employed survey and questionnaire as the data collection techniques. The sample consisted of 872 parents with children aged 17 and below. A statistical analysis was performed using SPSS software. A mixture of descriptive and inferential statistics were used during the analysis method. The finding shows that parental awareness of the cyber threats is at the medium level and still need to be improved to promote cyber safety. Early exposure to parental awareness on cyber threats would aid in opening up knowledge about cyber security among parents.